Pediatric sinonasal and skull base lesions. Issue 2 (1st June 2020) - Riley, Charles A.; Soneru, Christian P.; Overdevest, Jonathan B.; Otten, Marc L.; Gudis, David A.
Abstract : Pediatric skull base lesions are complex and challenging disorders. Safe and comprehensive management of this diverse group of disorders requires the expertise of an experienced multidisciplinary skull base team. Adult endoscopic skull base surgery has evolved due to technologic and surgical advancements, multidisciplinary team approaches, and continued innovation. Similar principles continue to advance the care delivered to the pediatric population. The approach and management of these lesions varies considerably based on tumor anatomy, pathology, and surgical goals. An understanding of the nuances of skull base reconstruction unique to the pediatric population is critical for successful outcomes.